1998
DOI: 10.1016/s0741-5214(98)70263-0
|View full text |Cite
|
Sign up to set email alerts
|

The clinical course of asymptomatic mesenteric arterial stenosis

Abstract: Patients with significant three-vessel mesenteric arterial stenosis should be considered for prophylactic mesenteric arterial reconstruction. Mesenteric arterial reconstruction should be routine when these patients undergo aortic reconstruction for aneurysmal or occlusive disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
130
1
16

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(147 citation statements)
references
References 2 publications
0
130
1
16
Order By: Relevance
“…This risk is increased in subjects with 2 and 3 vessel CSD. In the study by Thomas et al 4.5% of patients with three-vessel CSD developed CSS and another 1.5% died of ASS after a follow-up of an average of 2.6 years [9] . In the Detroit experience, of the 23 patients with severe acute intestinal ischemia studied between 1963 and 2000, 12 (52%) patients had undetected CSS symptoms well before presentation [14] .…”
Section: Epidemiologymentioning
confidence: 93%
See 1 more Smart Citation
“…This risk is increased in subjects with 2 and 3 vessel CSD. In the study by Thomas et al 4.5% of patients with three-vessel CSD developed CSS and another 1.5% died of ASS after a follow-up of an average of 2.6 years [9] . In the Detroit experience, of the 23 patients with severe acute intestinal ischemia studied between 1963 and 2000, 12 (52%) patients had undetected CSS symptoms well before presentation [14] .…”
Section: Epidemiologymentioning
confidence: 93%
“…In a 30-year-old angiographic study of 713 patients, 5% of the splanchnic arteries were occluded and in 70% of these occlusions the IMA was involved [8] . In a retrospective study including 980 patients with a mean age of 68 years who underwent angiography for various indications, 8% had significant stenoses of at least one splanchnic artery [9] . In a screening study with duplex ultrasonography in 553 healthy elderly subjects with a mean age of 84 years, stenoses in the celiac artery (CA) or superior mesenteric artery (SMA) were found in 18% [10] .…”
Section: Epidemiologymentioning
confidence: 99%
“…Reiner et al (cited in Dick et al, 1967 [9]) found that 46 of the 88 patients had severe atherosclerosis in aorta, 15 of them had the severest grade of mesenteric artery disease and 10 of them had little or no mesenteric artery disease [9,12]. Thomas et al [27] examined 980 abdominal aortograms and categorised the stenoses of the CT, SMA and IMA in three groups: mild (1-49%), moderate (50-74%) and severe (75-99%) stenoses. They studied the moderate and the severe groups and found that stenosis occurred more frequently in CT (96%) than in the SMA (50%) and IMA (57%) [27].…”
Section: The Burden Of the Atherosclerotic Plaquesmentioning
confidence: 99%
“…Thomas et al [27] examined 980 abdominal aortograms and categorised the stenoses of the CT, SMA and IMA in three groups: mild (1-49%), moderate (50-74%) and severe (75-99%) stenoses. They studied the moderate and the severe groups and found that stenosis occurred more frequently in CT (96%) than in the SMA (50%) and IMA (57%) [27]. Valentine et al [29] used the same method for the classification of the degree of arterial stenosis; 27% of the 205 male patients had at least one severe mesenteric artery stenosis, 25% had severe stenosis in CT, 6% had severe stenosis in SMA and 24% had moderate and 40% of them had severe renal artery stenosis.…”
Section: The Burden Of the Atherosclerotic Plaquesmentioning
confidence: 99%
“…Although most of the symptomatic patients have two out of three vessels involvement, the revascularization procedure should be considered in patients with documented critical stenosis in at least one major mesenteric vessel and in which other causes for chronic abdominal pain have been excluded. The indication for revascularization surgery in asymptomatic patients is not clear but it may be considered in asymptomatic patients who are submitted to aortic reconstruction for aortoiliac occlusive disease with significant mesenteric occlusion as they have an increased risk of mesenteric gangrene after surgery [72]. Often bypass grafting of the superior mesenteric artery alone instead of complete vascularization is an effective and durable procedure for treatment of intestinal ischemia [73].…”
Section: Treatmentmentioning
confidence: 99%